Experimental Investigation of Effects of Coastal Morphology on N-Waves - Bağci, Taylan; Kabdaşli, M. Sedat (Istanbul University, 2015)
A Leading Depression N-wave which consists of a negative and a positive amplitude solitary wave was generated with the help of a special designed wave pallet at Istanbul Technical University Hydraulic Laboratory. In addition, generated N-Wave was verified by using verification of related analytical equations. Furthermore, the wave flume was narrowed by narrowing angles of 5°, 10° and 15° for analogy to morphology changes in coastal areas. It was determined that water level differences and phase shifts occurred to the narrowing effects.
Keywords: N-Wave; Leading Depression N-wave; Solitary Wave; Tsunami